The Future We Create: Fictional Expectations as a Tool of Social Dynamics - Belyavskiy Boris (Экономическая социология, 2019)
This paper is a review of Imagined Futures: Fictional Expectations and Capitalist Dynamics, written by Jens Beckert and published in 2016. Prof. Beckert leads the Max-Plank Institute for the Study of Societies in Cologne. His works are in the fields of new economic sociology, economic anthropology and valuation studies. The last approach largely owes its existence to Beckertian theorizing. Imagined Futures highlights temporal perception in capitalist societies and the role of future expectations in the processes of capitalist dynamics. Beckertian theses also justify the importance of valuation studies and revise the role of economic forecasts. According to his central idea, economic forecasts cannot provide reliable future predictions due to the ontological uncertainty described by economic theory itself. Instead of looking into the future, the main function of forecasts is posited to be the coordination of social actions. The reduction of uncertainty provided by economic forecasts is essential for effective market function and the stability of social dynamics. This review proposes an interpretation of the theories outlined in the book and seeks to emphasize the importance of the author’s conclusions for valuation studies, new economic sociology and especially for studying the performative side of economic theory. The first part of the paper suggests the deeper historical roots of Imagined Futures. Next, the alternative philosophical frame for fictional expectations is discussed, and a systematization of fictional expectations is proposed. The paper’s second part problematizes capitalistic production and consumption described by Beckert as the foundation of the modern social order. Additionally, an ontological sense of future planning and capitalist dynamics is introduced in the context of symbolic consumption. The paper finishes by describing another aspects of performativity made by models of economic theory.